Non-targeted characterization of dissolved organic matter from a wastewater treatment plant by FT-ICR-MS: A case study of hospital sewage. (August 2022) - Gan, Shuchai; Wu, Peishan; Song, Yumei; Guo, Pengran; Cai, Nan; Yuan, Fei; Yang, Qiuxia; Wu, Ying; Liu, Ning; Pan, Jiachuan
Abstract: Hospitals generate large volumes of wastewater. Dissolved organic matter (DOM) in wastewater effluent can act as precursors of disinfection by-products, transporter of pollutants, and affect the performance of treatment plants. This study aims to characterize the composition of DOM in medical wastewater and investigate the selectivity of the hospital treatment plant in the removal of DOM. DOM was characterized by Fourier-transform ion-cyclotron resonance mass spectrometry (FT-ICR-MS) and excitation-emission matrix fluorescence spectroscopy (EEMs). DOM of medical wastewater was dominated by aliphatic and highly unsaturated compounds, a feature that is remarkably different from that of natural DOM. In the membrane bioreactor (MBR) unit, more CHNO compounds and highly unsaturated compounds were formed. After disinfection, the highly unsaturated and humic-like compounds were reduced, accompanying a decrease in aromaticity. After reverse osmosis, the highly unsaturated and CHO compounds were concentrated and removed. These steps were complementary in the removal of DOM, suggesting effective transformation and elimination of DOM. This study contributes to a better understanding of the features of DOM in medical wastewater and treatment plant performance in the removal of DOM, which is indispensable for the large-scale design and application of technologies for hospital wastewater treatment, especially in the context of the COVID-19 pandemic. Graphical abstract: Unlabelled Image Highlights: A database of DOM in medical sewage with more than 10, 000 formulae identified by FT-ICR-MS; Medical DOM was dominated by aliphatic and highly unsaturated compounds; MBR, disinfection, and RO unit are complementary in removing DOM in hospital sewage